2011
DOI: 10.1029/2011ja016789
|View full text |Cite
|
Sign up to set email alerts
|

On the divergence of the auroral electrojets

Abstract: [1] The current configuration in the auroral region is known to consist typically of downward and upward field-aligned current (FAC) sheets, connected in the ionosphere by meridional Pedersen currents, while divergence free electrojets (EJs) flow azimuthally as Hall currents. This configuration of the auroral current circuit was introduced by Boström (1964) and labeled as "Type 2," while he suggested also an alternative "Type 1" configuration, with filamentary FACs connected in the ionosphere by azimuthal Pede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Our example event was a Swarm crossing of a morning sector auroral arc with 1‐D properties (i.e., negligible azimuthal gradients and vanishing eastward electric field) allowing SECS analysis with single satellite electric field data. Analysis of more complicated arc cases, where, e.g., the Hall and Pedersen current systems are coupled with each other [ Marghitu et al , ], is left for future studies with electric field data from two Swarm satellites. In our case the structure of the derived conductances, electric fields, and currents associated with the arc were shown to be in good agreement with those expected for morning sector arcs: upward FAC, enhanced Hall and Pedersen conductances, and relatively weak electric field coincided with the arc.…”
Section: Discussionmentioning
confidence: 99%
“…Our example event was a Swarm crossing of a morning sector auroral arc with 1‐D properties (i.e., negligible azimuthal gradients and vanishing eastward electric field) allowing SECS analysis with single satellite electric field data. Analysis of more complicated arc cases, where, e.g., the Hall and Pedersen current systems are coupled with each other [ Marghitu et al , ], is left for future studies with electric field data from two Swarm satellites. In our case the structure of the derived conductances, electric fields, and currents associated with the arc were shown to be in good agreement with those expected for morning sector arcs: upward FAC, enhanced Hall and Pedersen conductances, and relatively weak electric field coincided with the arc.…”
Section: Discussionmentioning
confidence: 99%
“…As it was mentioned above (see section 3), the asymptotically path‐connected behavior is possible for the Hall current in the auroral ionosphere. It is known that Hall current flows in auroral arcs [ Haerendel et al , ; Frey et al , ; Marghitu et al , ]. The multiple arcs system is observed often rather than one auroral arc.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
“…For so-called high-top models, with upper boundary in the thermosphere, the boundary conditions can be defined by empirical models based on satellite data (e.g. Marsh et al, 2004), which depend on geomagnetic indices, day of the year, and solar flux. However, current models are based on temporally limited data and do not cover full solar cycles and/or differences between solar cycles, and recent studies indicate a need for improvements (Hendrickx et al, 2018;Kiviranta et al, 2018).…”
Section: Precipitation-driven Chemistrymentioning
confidence: 99%
“…By using the EISCAT ISR measurements, it has been established that auroral arcs are often associated with narrow intense electric fields just outside of the auroral arcs and related increased electron densities due to auroral electron precipitation (Aikio et al, 2002). Cluster satellite measurements showed that those electric fields develop rapidly in a timescale of minutes (Marklund et al, 2001;Aikio et al, 2004). Additionally, intense flow channels of ionospheric plasma have been found on the dayside in the cusp region (Oksavik et al, 2004), in the polar cap (Nishimura et al, 2014), and at high latitudes on the nightside in association with magnetospheric bursty bulk flows (Pitkänen et al, 2013).…”
Section: Incoherent Scatter Radarsmentioning
confidence: 99%